Human equilibrative nucleoside transporter‐1 expression is a predictor in patients with resected pancreatic cancer treated with adjuvant S‐1 chemotherapy. Issue 2 (19th December 2019) - Okamura, Yukiyasu; Yasukawa, Satoru; Narimatsu, Hiroto; Boku, Narikazu; Fukutomi, Akira; Konishi, Masaru; Morinaga, Soichiro; Toyama, Hirochika; Kaneoka, Yuji; Shimizu, Yasuhiro; Nakamori, Shoji; Sata, Naohiro; et al.
Abstract: The high expression of human equilibrative nucleoside transporter‐1 (hENT1) and the low expression of dihydropyrimidine dehydrogenase (DPD) are reported to predict a favorable prognosis in patients treated with gemcitabine (GEM) and 5‐fluorouracil (5FU) as the adjuvant setting, respectively. The expression of hENT1 and DPD were analyzed in patients registered in the JASPAC 01 trial, which showed a better survival of S‐1 over GEM as adjuvant chemotherapy after resection for pancreatic cancer, and their possible roles for predicting treatment outcomes and selecting a chemotherapeutic agent were investigated. Intensity of hENT1 and DPD expression was categorized into no, weak, moderate or strong by immunohistochemistry staining, and the patients were classified into high (strong/moderate) and low (no/weak) groups. Specimens were available for 326 of 377 (86.5%) patients. High expression of hENT1 and DPD was detected in 100 (30.7%) and 63 (19.3%) of 326 patients, respectively. In the S‐1 arm, the median overall survival (OS) with low hENT1, 58.0 months, was significantly better than that with high hENT1, 30.9 months (hazard ratio 1.75, P  = 0.007). In contrast, there were no significant differences in OS between DPD low and high groups in the S‐1 arm and neither the expression levels of hENT1 nor DPD revealed a relationship with treatment outcomes in the GEM arm. The present study did not show that the DPD and hENT1 are useful biomarkers for choosing S‐1 or GEM as adjuvant chemotherapy. However, hENT1 expression is a significant prognostic factor for survival in the S‐1 arm. Abstract : In the S‐1 arm, the median overall survival (OS) with low hENT1, 58.0 months, was significantly better than that with high hENT1, 30.9 months (hazard ratio 1.75, P  = .007). In contrast, there were no significant differences in OS between DPD low and high groups in the S‐1 arm and neither the expression levels of hENT1 nor DPD revealed a relationship with treatment outcomes in the GEM arm.